2019
DOI: 10.1159/000499433
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Frequently Used Antihypertensive Drugs on Wound Healing in vitro

Abstract: Background: The number of patients who has a daily intake of antihypertensive drugs is rising, due to an also rising prevalence of lifestyle diseases. Interestingly, knowledge about effects of these drugs in terms of wound healing is low. Objective: Based on a few differing studies, the idea arose that antihypertensives may have side effects on wound healing. Methods: Five antihypertensive drugs from different substance classes (metoprolol, amlodipine, ramipril, hydrochlorothiazide, candesartan) were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…CAP down-regulated the expression of the insulin-like growth factor receptor and phosphorylated mitogen-activated protein kinases, resulting in decreased collagen synthesis [39]. In addition, ramipril has been reported to increase the expression of caspase 3 in fibroblasts in a 3D wound model and adversely affects wound healing [40]. In contrast, many phenolics with antioxidant capacity have been known to promote wound healing by regulating the inflammatory stage of the wound healing process by scavenging ROS [41].…”
Section: Discussionmentioning
confidence: 99%
“…CAP down-regulated the expression of the insulin-like growth factor receptor and phosphorylated mitogen-activated protein kinases, resulting in decreased collagen synthesis [39]. In addition, ramipril has been reported to increase the expression of caspase 3 in fibroblasts in a 3D wound model and adversely affects wound healing [40]. In contrast, many phenolics with antioxidant capacity have been known to promote wound healing by regulating the inflammatory stage of the wound healing process by scavenging ROS [41].…”
Section: Discussionmentioning
confidence: 99%
“…Every other day, during replacement of wound dressings, we measured deep tissue oxygen saturation (i.e., near-infrared [NIR] perfusion), superficial hemoglobin oxygen saturation (StO 2 ), hemoglobin distribution (i.e., tissue hemoglobin index [THI]), and tissue water distribution (i.e., tissue water index [TWI]) using a modern hyperspectral imaging (HSI) camera device [19][20][21]. These parameters provide insights into the biological mechanisms of the healing process and, thus, allow a quantification in the context of the 3 stages of wound healing: inflammation, proliferation, and remodeling [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…2 5,9,10 Amlodipine toxicity results in a negative inotropic effect and bradycardia in isolated heart preparation, and apoptosis in uveal malignant melanoma and human fibroblasts. 11 14 A previous study showed that lipid emulsion attenuated apoptosis in cardiomyoblasts induced by the phenylalkylamine calcium channel blocker verapamil at toxic doses. 15 It has been reported that phosphoinositide-3 kinase and ATP-sensitive potassium channels are involved in cardiac protection.…”
Section: Introductionmentioning
confidence: 99%